Developing quality assurance in Yemeni universities in light of the knowledge management (مجلة جامعة سرت للعلوم الانسانية, 2023)
The study aimed to develop quality assurance in Yemeni universities and build a proposed vision that includes identifying development requirements in light of the knowledge management approach, by identifying the reality of quality assurance in Yemeni universities, the concept of knowledge management in universities and the benefits of its application, its operations, and the most important models for knowledge management and its role in Ensuring the quality of universities, and the requirements for their application in universities; In order to provide an appropriate conception of quality assurance in Yemeni universities. The study relied on the descriptive approach to study indicators, official reports, and scientific studies on the status of quality assurance in Yemeni universities. It reached many results, the most important of which is that the requirements for developing quality assurance in the light of the knowledge approach are concentrated in the requirements: administrative-organizational-leadership-technological-organizational culture requirements.
Keywords: development; quality assurance; knowledge management